Hegemoni “Agama Resmi” Dan Ambiguitas Kebebasan Berkeyakinan Penghayat Sapta Darma Di Jember, Jawa Timur - Widianto, Ahmad Arif; Hasanah, Fitriatul (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Violations of freedom of religion or belief continue to pose significant challenges to interfaith cooperation. Adherents of indigenous beliefs frequently experience such violations despite the legal and formal guarantees of their religious rights. Believers, as a minority group, are often marginalized and subjected to restrictions, even though their identity is recognized by Constitutional Court Decision Number 97/PUU-XIV/2016. This article examines the hegemonic relationship between